Indirect Relations between Language and Behavior Problems in Preschoolers: The Role of Executive Difficulties. Issue 6 (24th October 2022) - Spataro, Pietro; Cerutti, Rita; Laghi, Fiorenzo; Longobardi, Emiddia
Abstract: The present study investigated the concurrent relations between language ability, executive difficulties, and behavior problems in a sample of 142 preschoolers ranging in age between 3 and 6 years of age. Language skills were assessed with a direct task, whereas ratings of executive difficulties and behavior problems were obtained from teachers. Regression analyses indicated that difficulties in flexibility and inhibitory self-control were positively associated with internalizing problems, and difficulties in inhibitory self-control were positively associated with externalizing problems. The associations between emergent metacognition and internalizing problems and between inhibitory self-control and externalizing problems were both moderated by sex, being stronger in boys than in girls. Lastly, language had indirect effects on internalizing problems by decreasing children's difficulties in flexibility, as well as on externalizing problems by decreasing children' difficulties in inhibitory self-control. Overall, these findings support the idea that low language skills may interfere with preschoolers' ability to exploit the executive functions of inner language to self-regulate their own behaviors, especially in boys.